2014
DOI: 10.1186/1471-2407-14-901
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic inactivation of ST6GAL1 in human bladder cancer

Abstract: BackgroundPosttranslational protein modifications are known to modulate key biological processes like proliferation and apoptosis. Accumulating evidence shows that ST6GAL1, an enzyme that catalyzes the transfer of sialic acid onto galactose-containing substrates, is aberrantly expressed in various cancers and may affect cell motility and invasion. This is the first study to describe ST6GAL1 expression and regulation in human bladder cancer.MethodsST6GAL1 mRNA expression levels in human cell lines (UROtsa, RT4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 32 publications
2
31
0
Order By: Relevance
“…Absorbance (A 490 ) was measured at 490 nm on an enzyme-linked immunosorbent assay plate reader. The inhibition rate was calculated using the following formula: cell proliferation inhibition rate = (the average of A 490 values from the control group - the average of A 490 values from the experimental group)/the average of A 490 values from the control group × 100% [22]. All experiments were performed in triplicate and more than three wells were used for each treatment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Absorbance (A 490 ) was measured at 490 nm on an enzyme-linked immunosorbent assay plate reader. The inhibition rate was calculated using the following formula: cell proliferation inhibition rate = (the average of A 490 values from the control group - the average of A 490 values from the experimental group)/the average of A 490 values from the control group × 100% [22]. All experiments were performed in triplicate and more than three wells were used for each treatment.…”
Section: Methodsmentioning
confidence: 99%
“…A complete medium containing 800 μg/ml G418 was added, and stably expressed transfected cells were obtained by being screened for 2 weeks. Strains were acquired by expanded culture and stored in liquid nitrogen prior to further analysis [22]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is even less studied than transcription factor binding to glycogenes, although a recent study analyzing DNA methylation of 86 glycogenes suggests a positive correlation between the promoter methylation status of glycogenes and expected tumor-associated glycan structures [17]. A handful of studies have also shown a direct interaction between the methylation status of specific glycogenes and glycogene expression [1821]. In this regard, the methylation of the α(2,3)sialyltransferase ST6Gal1 promoter was shown to silence expression of the ST6Gal1 transcript in bladder cancer [18], confirming an earlier report in breast cancer showing methylation-dependent silencing of this glycogene [22].…”
Section: Multi-level Regulation Of Glycosylationmentioning
confidence: 99%
“…Expression reduced by epigenetic inactivation in bladder cancer (Antony et al 2014). Linked to EMT transition and malignancy (Lu et al 2014) Androgen regulated and linked to prostate cancer cell viability B4GALT1 Late processing of N-glycans (transfers a galactose residue to terminal N-acetylglucosamine)…”
Section: :3mentioning
confidence: 99%